Hollowing out the middle? Remittances, poverty, and income inequality in Nigeria. (2nd September 2022) - Bang, James T.; Mitra, Aniruddha; Wunnava, Phanindra V.
ABSTRACT: This paper investigates the impact of remittances on poverty and inequality in Nigeria. In contrast to the existing literature, our methodology of instrumental variable quantile regression (IVQR) explicitly demonstrates the differential marginal impact of remittances for households at different levels of the conditional expenditure distribution. In tracing this heterogeneous impact, we are further able to address the effect of remittances on poverty and inequality simultaneously in one econometric model. Our results based on the Nigerian Migration Household Survey 2009 show that remittances reduce poverty by increasing household expenditures reveal a positive marginal impact of remittances at all but the highest quantiles of the conditional distribution of household expenditure, with the impact being the greatest up to the 12 th quantile. While this unambiguously supports the poverty alleviation role of remittances documented in the literature, the distributional impact is more nuanced: The marginal effect of remittances follows a U-shape over most of the household expenditure distribution, which suggests that remittances may 'hollow out' the middle class. Specifically, households lying between the 13 th to the 35 th quantile gain less from receiving remittances than households on either side of this range.